PENGARUH PEMBELAJARAN BERBASIS MASALAH DENGAN STRATEGI THINK TALK WRITE TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS DAN SELF EFFICACY SISWA - Dita Lusiana; Eka Setyaningsih (AlphaMath : Journal of Mathematics Education, 2018)
The purpose of this research is to find: 1). Student's achievement in mathematics representation ability who followed the learning process using Think, Talk, Write strategy; 2).  Student's achievement in self-efficacy who followed the learning process using Think, Talk, Write strategy; 3). Whether a student's achievement in mathematics representation ability who followed the learning process using Think, Talk, Write strategy is better than a student who followed a direct learning process; 4). Whether a student self-efficacy who followed the learning process using Think, Talk, Write strategy is better than a student who followed a direct learning process.The population of this research is a whole of the 8thgrade students from Junior High Schools from Purbalingga. The sampling process is determined by a cluster random sampling technique so that the research can obtain the experiment class in which learning proses are using the TTW strategy with 71,81 rate, meanwhile, students who are following direct learning are around 62,94. Based on the student self-efficacy questionnaire who followed learning process with the TTW strategy are 74,37 rate, meanwhile students who are following direct learning are around 66,37. The data analysis using independent sample T-Test to test one right side. The result of the research shows that student's achievement in mathematics representation ability who followed the learning process using the TTW strategy is better than a student who followed a direct learning process. Student self-efficacy who followed the learning process using the TTW strategy is better than a student who followed a direct learning process.